Dimensi Contempt Of Court Versus Hak Imunitas Advokat dalam Sistem Peradilan Indonesia - Kahar, Kahar; Wulan, Retno (JISH: Jurnal Ilmu Syariah dan Hukum, 2025)
This article examines The Dimension of Contempt of Court Versus the Immunity Rights of Advocates in the Indonesian Judicial System.” Recently, court trials have attracted widespread public attention not because people attend the courtrooms physically, but because the proceedings are now accessible through electronic systems, allowing anyone to watch trials, including the legal debates and arguments between public prosecutors and defense attorneys (advocates), or between plaintiffs or their legal representatives (advocates) and defendants or their counsel (advocates). These debates sometimes spiral out of control, resulting in the use of insulting or degrading language among participants, which is considered to undermine the authority and dignity of the court a situation referred to as contempt of court. Consequently, advocates have been reported for such behavior. This paper therefore examines three main issues: first, how the judicial system and the concept of contempt of court operate in Indonesia; second, how contempt of court relates to the immunity rights of advocates; and third, what factors influence advocates to commit acts that may constitute contempt of court during trials. This study employs empirical legal research with a conceptual approach, utilizing secondary data consisting of: (1) primary legal materials, which include fundamental norms such as the 1945 Constitution of the Republic of Indonesia, statutory regulations, uncodified legal materials, and jurisprudence; (2) secondary legal materials, which explain primary legal materials, such as draft laws, research findings, and scholarly works in the field of law; and (3) tertiary legal materials, which provide guidance or explanations of both primary and secondary legal materials, such as dictionaries and encyclopedias. The findings reveal that: (1) Indonesia’s judicial system adheres to a “combined system”, and contempt of court refers to any act that may be considered to humiliate, obstruct, hinder, or undermine the duties of the judiciary; (2) the immunity rights of advocates and the concept of contempt of court are interrelated and mutually supportive in maintaining the dignity and authority of the judiciary; and (3) acts of contempt of court committed by advocates during court proceedings are influenced by several factors, including: (a) the structure of the legal system, (b) the substance of the law, and (c) the legal culture.